Financial Technology-Based Sharia Cooperatives Development Strategy in Indonesia - Nawir Yuslem; Soemitra, Andri; Barus, Elida Elfi (LPPM, Universitas Islam Syarifuddin Lumajang, 2022)
The economic development instruments normally used in Indonesia are the state, cooperatives, and private companies established for social welfare. Those related to Sharia are characterized by the presence of Sharia cooperatives which are observed to be growing rapidly despite several obstacles in terms of capital and innovation caused by the existence of financial technology (fintech). This phenomenon led to the conduct of this research to analyze development of a Sharia cooperatives financing model based on Islamic Fintech. The methodology applied was qualitative research using the ISM method. The participants include experts from AFSI, Fintech, Academia, the Office of Cooperatives and SMEs, OJK, KNEKS, and Sharia Cooperatives. The results showed nine elements used as the keyword to develop Sharia cooperatives as an economic development instrument for the MSMEs communities being assisted by unbankable cooperatives in Indonesia.